Interdisciplinary Application of Telecommunications in the Modern World - Kovačević, Dražen; Macura, Arijana; Maković, Branko (Promet - Traffic&Transportation, 2012)
Communications have become irreplaceable part of eveJydayaccivities. Mobile communication is gaining in importancedue to the mobility of terminals and persons. Telecommunications,computer and media indus fly are getting connected andthe chain of values shifts from components to overall solutions.Possibilities offered by information technology are limitless,and its application enables better working conditions since theykeep humans away from dangerous working places and facilitateheavy tasks. The applications in the field of informationand communication technology make it possible to drive fromone end of the continent to another without needing any maps.The computer onboard a vehicle can choose the best directionand adapt to the travelling conditions.